Bridging Expectations and Experiences: Exploring Teacher–Learner Dynamics in the BIPA Program - Nurlaily Nurlaily; Maya Marsevani; Yowina Trisannia; Rizky Putra (JOLLT Journal of Languages and Language Teaching, 2026)
This study explored the alignment between teacher expectations and learner experiences of the BIPA (Bahasa Indonesia for Foreign Speaker) program. Since the demand for BIPA is increasing, these dynamics have to be understood in order to improve language learning outcomes. The research employed a mixed methods approach in a university in Batam and involved eight teachers and nine learners of different cultural backgrounds. Interviews, questionnaires and observations were used to gather data. The partial alignment of teacher expectations and learner experiences were found. Both focus on speaking skills and give regular feedback, but they differ in how to teach, how fast they should pace the lesson, and how to engage learners. The challenges that were faced include grammar, pronunciation and understanding spoken instructions. The research concluded that these gaps are addressed through differentiated instruction, interactive activities and culturally responsive teaching. These changes might increase learner satisfaction and program effectiveness. Research findings made clear the need for more learner centered approaches and provide important guidance for stakeholders and future studies to improve BIPA programs.